Serum peptidomic screening identified circulating peptide biomarkers predictive for preeclampsia - Zhao, Shenglong; Yin, Chenghong; Zhai, Yanhong; Jia, Zhaoxia; Su, Shaofei; Lu, Yifan; Meng, Lanlan; Li, Chunbo; Liu, Xiang; Cong, Yuting; Li, Youran; Liu, Ying; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Reliable biomarkers are needed to improve preeclampsia (PE) prediction accuracy. With the investigational tool of peptidomics, we aimed to identify and validate potential serum peptide biomarkers in cohorts suspected for PE development in middle or late pregnancy. Methods Totally 195 serum samples were prospectively collected from pregnant women with PE-related syndromes who were followed up for PE development until delivery. Serum peptidomic analysis was performed in the discovery cohort of 115 samples using matrix-assisted laser desorption ionization-time of flight coupled with Linear Trap Quadropole Orbitrap mass spectrometry. The candidate biomarkers were further validated using an in-house developed liquid chromatography tandem mass spectrometry (LC-MS/MS) method in an independent validation cohort of 80 serum samples. Results We identified 8 peptides that were differentially expressed and originated from fibrinogen alpha chain (FGA), inter-alpha-trypsin inhibitor heavy chain H4 (ITIH4) and complement component 3. In the subsequent LC-MS/MS quantitation analysis, the levels of the three peptides (FGA-1033.4, ITIH4-2026.9, ITIH4-2051.1) exhibited a significant difference between the PE-positive and PE-negative groups. Further, the three-peptide panel yielded an area under the ROC curve (AUC) of 0.985 [95% confidence interval (CI) 0.965–1.000] and 0.923 (95% CI 0.845–1.000) in the discovery and validation cohorts respectively, with negative predictive values of 98.1–98.8% and positive predictive values of 73.1–85.3% that were much improved when compared with that of soluble fms-like tyrosine kinase-1/placental growth factor (sFlt-1/PlGF) ratio. Conclusions We have discovered and validated a novel three-peptide biomarker panel predictive for the occurrence PE in pregnant women.